Studi Perbandingan Hukum “Plea Bargaining System” di Amerika Serikat dengan “Jalur Khusus” di Indonesia - Rifi Hermawati (Jurnal Hukum Lex Generalis, 2023)
Plea Bargaining developed in the United States of America. It is a negotiation between the public prosecutor and the accused or their defender so that the process of resolving criminal cases is carried out quickly and effectively. Plea Bargaining became the basis for the formation of the concept of “special lane” in Indonesia in article 199 of the Criminal Procedure Code Bill. Both of these concepts carry the short examination mechanism. The difference is in the "special lane" the defendant cannot negotiate with the prosecutor regarding charges or threats of punishment because the defendant's guilty plea was made in front of the judge during the trial and the “special line” is used for crimes that have a threat of no more than 7 years while Plea Bargaining applies to all types of crimes.